Ibnu Miskawaih: Philosophical Thoughts On Moral Education And Its Relevance To Contemporary Islamic Education - Handal Pratama Putra; Solihah Hayeesama-ae (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The purpose of this study is to discuss Ibnu Miskawaih’s concept on the philosophical thoughts of moral education and its relevance to contemporary Islamic education in Indonesia. Ibn Miskawaih is a Muslim scholar who has composed many works on ethical philosophy. This research is a qualitative descriptive and a kind of literature study. The method used content analysis. The results and discussion explained that Ibn Miskawaih has the concept of morality, that states the condition of the human soul that encourages to do an act without prior consideration and calculation. Ibnu Miskawaih formulated about moral education, it begins with the method of moral education, moral education material and the purpose of moral education. The relevance of Ibn Miskawaih's philosophical thoughts to contemporary Islamic education is considered reasonable and relevant in terms of the objectives, materials, and methods of Islamic education, that to realize individuals developing noble characters and obeying the Islamic values.Keywords: Philosophy, Moral Education, Ibnu Miskawaih